Հայ ժողովրդական կենդանապատում հեքիաթի ժանրային-կառուցվածքային առանձնահատկությունները - Լ. Է. Մկրտումյան (ՀՀ ԳԱԱ հրատ.)
Важной жанровой характеристикой рассматриваемых сказок является то, что в них животные становятся условными носителями человеческих характеров. При этом в сказках о животных нет аллегорий, столь характерных для басен, поскольку сюжет сказок развивается на основе отношений реальных сказочных героев: лисы, волка, зайца и т.д. Сказки о животных отличаются лаконичностью изложения текстов, в них преобладает диалог, который служит основой построения фольклорного сюжета и средством отражения характеров. An important genre peculiarity of the tales under consideration is that the animals become conditional bearers of human characters, and are used to discribe human relations and actions. At the same time, the animal tale is deprived of an allegory, characteristic of the parable, as the relationships of tales real heroes, i.e. wolf, fox, rabbit and others are at the very core of the plot development. The animal tales are based on the tricks-dexterity-deception,which forms their main motives and suggests the archaism of their origin. Animal tales are remarkable for the laconism and conciseness of the texts, in which the dialogue is prevalling. The dialogue forms both the foundation for the construction of folk text, and is a path for creation and revelation of the characters.
Keywords: Geography; Anthropology; Recreation; Language and Literature; Folklore; Literature